Translation strategies of idioms used in the translation into Spanish of the young adult novel “Bajo la misma estrella” - Camacho Fuentes, Brenda (2025)
The present research seeks to identify and analyze the translation strategies of idioms that are used in the translation into Spanish of the young adult novel “Under the Same Star”, written by John Green and published in 2012. For this purpose we will use as main theoretical framework Mona Baker’s proposals.